2017
DOI: 10.12998/wjcc.v5.i6.212
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations against respiratory infections in Arabian Gulf countries: Barriers and motivators

Abstract: AIMTo study the uptake, barriers and motivators of influenza, pneumococcal, meningococcal and pertussis vaccines among members of public in Arabian Gulf countries.METHODSA cross-sectional survey among the Gulf Cooperation Council (GCC) countries’ residents. Data collected electronically through a smartphone app. The survey variables aimed to investigate the respondents’ awareness about vaccines against influenza, pneumococcal, meningococcal and pertussis infections. Collected data concerning the respondents’ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…The results from this study found an overall vaccination rate of 12.6%. This vaccination rate is lower than the previous findings published among the general public, the military, pregnant women, and healthcare workers in Saudi Arabia; however, this study most closely resembles a recent study by Alqahtani et al in terms of study design, sample size, and vaccination rates [ 31 ]. An inoculation rate of 15% was reported in their cross-sectional survey among a sample of 1105 residents of Saudi Arabia.…”
Section: Discussionsupporting
confidence: 67%
“…The results from this study found an overall vaccination rate of 12.6%. This vaccination rate is lower than the previous findings published among the general public, the military, pregnant women, and healthcare workers in Saudi Arabia; however, this study most closely resembles a recent study by Alqahtani et al in terms of study design, sample size, and vaccination rates [ 31 ]. An inoculation rate of 15% was reported in their cross-sectional survey among a sample of 1105 residents of Saudi Arabia.…”
Section: Discussionsupporting
confidence: 67%
“…Studies show that the average vaccine uptake for a Saudi Arabian is 15%, which is lower than that of other Gulf countries such as Qatar, whose rate is 24%. [12] However, people who were at a higher risk of getting these diseases had a pneumococcal vaccine uptake of 25%. [12]…”
Section: Introductionmentioning
confidence: 99%
“…[12] However, people who were at a higher risk of getting these diseases had a pneumococcal vaccine uptake of 25%. [12]…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports on uptake of other recommended vaccines at Hajj also indicated that receiving pre-travel health advice was a considerable motivator for receiving vaccinations against other diseases [14,23]. Furthermore, in a large survey among residents of Gulf Cooperation Council countries, doctors' advice was the leading motivator for receipt of influenza vaccine [24]. Worksite immunization was shown to be effective in facilitating influenza vaccine uptake in Saudi Arabia [25].…”
Section: Discussionmentioning
confidence: 99%